Korelasi Dampak Covid-19 Dengan Era Society 5.0 di Bidang Pendidikan - Ratnanenci, Cici (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2021)
Covid-19 is a viral outbreak that is rampant in all corners of the world including in Indonesia. It certainly has an impact in various sectors of life, one of which is education, which forces us to use technology in all learning activities and demand human resource skills in various fields. It shows a correlation with the era of society 5.0 which is a concept of a technology-centered human-centered society. The purpose of this study is to show a link between the impact of Covid-19 and the era of society 5.0 in the field of education. The method that researchers use is a research library in the form of references from various sources on the internet. The results of this study show a fact that the impact of Covid-19 turns out to have a relationship in the form of self-habituation and simulation in the face of education in the era of society 5.0.